PENGARUH TINGKAT KERACUNAN ALUMUNIUM TERHADAP PERUBAHAN GULA YANG DIEKSUDASI OLEH PERAKARAN KEDELAI (GLYCINE MAX [L.] MERR.) - Timotiwu, Paul Benyamin (JURNAL AGROTROPIKA, 2010)
Around 7 ? 30 % of photosynthate produced by plants was exuded through the plant roots. Compounds exuded were in forms of polysaccharides, polypeptides, enzymes, and several secondary metabolic compounds. The presence of aluminum may cause an obstruction on seedling growth and establishment and significantly relate with sugars excreted by the plant roots. The mechanisms of sugars excretion by the plants was one among several means of the plants to overcome environmental toxicity. This research intended to (1) find out kind of sugars exuded by the soybean roots when underwent an aluminum toxicity; and (2) understand the effects of the increase of aluminum concentration on sugars exuded by the soybean roots. The research utilized a technique of aeroponic mist system. The treatments were arranged in a 3X2 factorial; the first factor was the aluminum concentration consisted of 0, 0.5, and 1 mM AlCl3. The second factor was the soybean varieties which were Slamet variety recommended resistant to Al and Burangrang variety susceptible to Al. The treatment combinations were applied in a split plot ? randomized complete-block design. To understand the effects of the increase in Al concentration and the differences of kind of sugars on the varieties, standard error of mean (SEM) statistics were used. The results of this research indicated that sugars exuded from the roots of Slamet and Burangrang soybeans which experienced Al toxicity were glcose (Glc) and galactose (Gal). Total exuded Glc from Slamet variety was 639.23 µg, whereas Burangrang variety was 899.41 µg. Total exuded Gal from Slamet variety was 404.78 µg whereas Burangrang variety was 489.85 µg. The pattern of sugar exudation was different between Slamet and Burangrang with the increase of Al concentration. The Slamet variety confirmed more tolerant than the Burangrang variety since the Slamet variety increased the exudation of Glc and Gal in response to the increased of Al concentration. This phenomenon was strengthened by the parameter responses of a lower decrease on root fresh and dry weights, and a lower percentage of killed plants. Key words: aerophonic mist system, aluminum, glucose, galactose, soybean